Cytotoxic effects of permethrin in oocytes of Rhipicephalus sanguineus (Acari: Ixodidae) fully engorged females: I. Direct or indirect action of the acaricide in germ cells? - Roma, Gislaine Cristina [UNESP]; Scopinho Furquim, Karim Christina [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Springer, 2011)
Given the wide use of synthetic chemicals to control ticks, this study evaluated the effects of the permethrin pyrethroid on oocytes of Rhipicephalus sanguineus fully engorged females in order to examine whether this compound, in addition to the proven neurotoxic effect, also acts directly on germ cells. The results revealed that permethrin effectively inhibits and/or interrupts the reproductive process of R. sanguineus. Exposed oocytes exhibited prominent structural changes such as altered shape of cells and germ vesicle (oocyte nucleus), cytoplasmic vacuolation, and decrease of yolk granules. The composition of the latter, however, was not altered. These findings confirm those already reported by Roma et al. (Food Chem Toxicol 48:825-830, 2010) demonstrating that permethrin acts on germ cells of R. sanguineus via direct absorption from the hemolymph by pedicel cells, or by the oocyte plasmic membrane. on the other hand, these results contradict studies reporting that acaricides act exclusively on the nervous systems of ticks and that all the changes in other organs are a result from the indirect action of these chemical compounds, because blocking of the nervous system would compromise the normal metabolism of other organs (dependent on sensory information).
Keywords: Rhipicephalus sanguineus; Ticks; Acaricide; Germ cells; Cytotoxicity